Optimizing Student Development through Effective Assessment Practices: Insights from School Counselors in Indonesia - Jumail, Jumail; Laisouw, Yusup; Mahaly, Sawal; Maswain, Maudianti (Guidance and Counseling Study Program, Pattimura University, 2024)
Since the advent of the Industrial Revolution 4.0, education has gained significant attention from academics and practitioners. The transformative initiatives introduced by Indonesia's Minister of Education and Culture, Nadiem Makarim, have reshaped the educational landscape, particularly through the